2022
DOI: 10.3390/bios12040220
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Microfluidic Platform for Physical and Immunological Detection and Capture of Circulating Tumor Cells

Abstract: CTCs (circulating tumor cells) are well-known for their use in clinical trials for tumor diagnosis. Capturing and isolating these CTCs from whole blood samples has enormous benefits in cancer diagnosis and treatment. In general, various approaches are being used to separate malignant cells, including immunomagnets, macroscale filters, centrifuges, dielectrophoresis, and immunological approaches. These procedures, on the other hand, are time-consuming and necessitate multiple high-level operational protocols. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 178 publications
1
13
0
Order By: Relevance
“…Because of the scarcity of CTCs, isolating enough CTCs is a crucial step for single-cell sequencing, which relies on the efficiency of enrichment and isolation of the system. With the advancement of microfluidic instruments in recent years, the enrichment and capture efficiency of most technologies can reach 80–90% or higher [ 12 ]. The CTC platforms based on microfluidic technology have better capture efficiency than other technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the scarcity of CTCs, isolating enough CTCs is a crucial step for single-cell sequencing, which relies on the efficiency of enrichment and isolation of the system. With the advancement of microfluidic instruments in recent years, the enrichment and capture efficiency of most technologies can reach 80–90% or higher [ 12 ]. The CTC platforms based on microfluidic technology have better capture efficiency than other technologies.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, microfluidic technology has developed more rapidly because of its many advantages, such as high throughput, low cost, high efficiency, precision and low sample consumption [ 30 ]. For example, Wang et al, have reported a capture efficiency about 81% and a high purity of 83% by using multifunctional microsphere-assisted inertial microfluidics to isolate fnRBCs [ 31 ].…”
Section: Microfluidics Technologies For Nipdmentioning
confidence: 99%
“…Due to advances in fabrication technique of microfluidic system, recovery rates of CRCs can reach 80–90% or higher for most systems [ 30 ]. Chromosomal aberrations can be detected using on-chip FISH.…”
Section: Isolation Of Fetal Cellsmentioning
confidence: 99%
“…In recent years, microfluidic devices have been increasingly utilized for different biophysical tasks, such as cell cultivation [ 1 , 2 , 3 , 4 , 5 ], cell separation [ 6 , 7 , 8 , 9 , 10 , 11 ], expansion of CTC from patient blood [ 12 , 13 , 14 , 15 , 16 , 17 ], flow cytometric analysis and cell manipulation [ 18 , 19 , 20 , 21 , 22 , 23 ], tissue engineering (Organ-On-a-Chip) [ 24 , 25 , 26 , 27 , 28 , 29 ], cell sorting and cell counting [ 30 , 31 , 32 , 33 ], and point of care (POC) diagnosis [ 34 , 35 , 36 , 37 , 38 , 39 ]. Many biochemical analyses can be screened at a faster rate in disease diagnosis [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%